TECHNOLOGICAL TECHNOLOGY TECHNOLOGY STUDENTS, WHAT PEDAGOGICAL PROBLEM - Калеков Расберген Кудайбергенович (Innovate Conferences, 2025)
In the community presented analysis of pedagogical scientific works, dedicated to creative activity, with the aim of highlighting key categories of the concept of "technical creativity of students" in higher educational institutions. Considered the relationship of technical creativity with categories of upbringing, education and teaching creativity, which allows Integrate the theory of creativity and pedagogy in this context.In the work the problem of insufficient use of innovative methods of teaching in most higher educational institutions, Hindering the development of technical creativity to the level of technical inventiveness. It is noted the key role of teaching methods in the success of scientific and technical creative activity of students and the importance of forming their Emotional needs in technical creativity through active methods, stimulating thinking.
Keywords: technical creativity of students, teaching methods, creative thinking.